2022
DOI: 10.1111/adb.13253
|View full text |Cite
|
Sign up to set email alerts
|

Oral oxycodone self‐administration leads to features of opioid misuse in male and female mice

Abstract: Use of prescription opioids, particularly oxycodone, is an initiating factor driving the current opioid epidemic. There are several challenges with modelling oxycodone abuse. First, prescription opioids including oxycodone are orally self-administered and have different pharmacokinetics and dynamics than morphine or fentanyl, which have been more commonly used in rodent research. This oral route of administration determines the pharmacokinetic profile, which then influences the establishment of drug-reinforcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 167 publications
1
16
0
Order By: Relevance
“…Newer systems typically involve the use of inexpensive, commercially available sensors and components controlled by either a standard computer or microcontrollers, such as an Arduino or Raspberry Pi. Recently, two versions of infrared (IR) photobeam-break sensor based systems have been a common choice for detecting rodent drink events in a home cage environment ( Frie and Khokhar, 2019 ; Godynyuk et al, 2019 ; Slivicki et al, 2023 ). The devices generated by these groups have filled many user needs, chiefly generating easy-to-use open-source designs that greatly improved the temporal resolution of drinking data.…”
Section: Introductionmentioning
confidence: 99%
“…Newer systems typically involve the use of inexpensive, commercially available sensors and components controlled by either a standard computer or microcontrollers, such as an Arduino or Raspberry Pi. Recently, two versions of infrared (IR) photobeam-break sensor based systems have been a common choice for detecting rodent drink events in a home cage environment ( Frie and Khokhar, 2019 ; Godynyuk et al, 2019 ; Slivicki et al, 2023 ). The devices generated by these groups have filled many user needs, chiefly generating easy-to-use open-source designs that greatly improved the temporal resolution of drinking data.…”
Section: Introductionmentioning
confidence: 99%
“…Slivicki et al. showed that mice voluntarily self-administer oxycodone; some mice even demonstrated drug taking that is resistant to aversive consequences ( 91 ), similar to OUD. While animal models have helped elucidate mechanisms, more studies that are focused on human subjects are needed.…”
Section: Hiv Opioids and Alterations To The Gut Microbiomementioning
confidence: 99%
“…This trend indicates an increasing need for animal models of liquid oral consumption. Opioids can be consumed orally by rodents, similar to alcohol consumption models. Increasingly there are other novel means for people to consume drugs. San Francisco recently (2018–2020) saw a shift in people who inject drugs (PWID) reporting decreased injections of heroin in favor of increased fentanyl smoking .…”
Section: The Gold Standard: a Necessary Shift To Consider Multiple Ro...mentioning
confidence: 99%